Novel Design of a Lowpass-Bandpass Diplexer with an Exceptional Performance Using Microstrip Meandrous Loaded Lines for Microwave Systems - Yahya, Salah I.; Abdel Hafez, Mohammed; Nouri , Leila; Zubir, Farid (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
A new microstrip lowpass-bandpass diplexer with exceptional performance characteristics is designed and analyzed. It includes microstrip meandrous thin lines loaded by solid cells. The diplexer achieves 0.058 dB and 0.013 dB low insertion losses (ILs) and 26.4% wide fractional bandwidth (FBW). Operating frequencies are obtained using a perfect mathematical method, which are verified by the simulation results. Having two equations that accurately predict the operating frequencies allows us to optimize the diplexer's performance by adjusting key parameters such as line lengths and widths. This helps in achieving the desired operating frequencies with minimal trial and error. It has 0.01 λg2 very compact size and exhibits low group delays at both channels, which make it appropriate for a varied range of applications requiring high precision and efficiency. Overall, this microstrip diplexer design offers a versatile and reliable solution for demanding RF and microwave applications.